Revitalising Martin Luther's Theological Thought for the Context of the Modern Church and Society - Mawikere, Marde Christian Stenly; Hura, Sudiria (International Journal of Education, Information Technology, and Others, 2025)
This article revisits the theological thought of Martin Luther, focusing on its relevance within the context of the modern church and society. Using literature review and content analysis methods, this study identifies key concepts in Luther's theology, such as salvation, Christian freedom, the sacraments, and the two kingdoms, while relating them to contemporary challenges, including social injustice and moral crises. The novelty of this research lies in the application of Luther's theological thought to current social issues, offering new insights into how the church can integrate moral and Gospel values to lead social change. This study provides an important contribution to renewing the relevance of Luther's teachings for the modern church.